2016
DOI: 10.1007/s10875-016-0279-0
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Health Resource Utilization in Patients with Primary Immunodeficiency Disease Prior to and Following 12 Months of Immunoglobulin G Treatment

Abstract: PurposeHealth-related quality of life (HRQOL) has not been examined in patients with predominant antibody deficiency both pre- and post-immunoglobulin G (IgG) treatment initiation. HRQOL and health resource utilization (HRU) were assessed in newly diagnosed patients with primary immunodeficiency disease (PIDD) pre- and 12 months post-IgG treatment initiation.MethodsAdults (age ≥18 years) completed the 36-item Short Form Health Survey, version 2; pediatric patients (PP)/caregivers completed the Pediatric Qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…High satisfaction and increased well-being resulting from combining treatment with daily life were shown, which were interpreted as promoting factors. Clinically relevant increases of HRQOL in physical health and in the mental health domain have been shown when patients with immunodeficiency receive replacement therapy (Routes et al, 2016). Espanol et al (2014) have found that home therapy regimens where patients self-administer their treatment may lead to improvements in HRQOL and treatment satisfaction.…”
Section: Promoting Factors In the Experience Of The Burden Of Treatmentioning
confidence: 99%
See 2 more Smart Citations
“…High satisfaction and increased well-being resulting from combining treatment with daily life were shown, which were interpreted as promoting factors. Clinically relevant increases of HRQOL in physical health and in the mental health domain have been shown when patients with immunodeficiency receive replacement therapy (Routes et al, 2016). Espanol et al (2014) have found that home therapy regimens where patients self-administer their treatment may lead to improvements in HRQOL and treatment satisfaction.…”
Section: Promoting Factors In the Experience Of The Burden Of Treatmentioning
confidence: 99%
“…Because patients with severe immunodeficiency require therapy indefinitely, the form of administration as well as setting in which the therapy takes place is an important factor that can affect patients’ health‐related quality of life (HRQOL). It has been found that patients with PID experience lower HRQOL scores, higher hospitalisation rates and increased limitations in their social activities, work and physical activity (Jiang, Torgerson, & Ayars, ; Routes et al., ). The goal of treatment was to individualise treatment regime to provide optimal medical outcomes and quality of life for all patients in need of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common variable immunodeficiency (CVID) is the most common primary immunodeficiency disease (PID). Most CVID patients receive immunoglobulin (Ig)G substitution, which has a significant impact on health-related quality of life [8,9]. The estimated prevalence of CVID is between 1 : 100 000 and 1 : 10 000 in the adult population [7].…”
Section: Introductionmentioning
confidence: 99%
“…The estimated prevalence of CVID is between 1 : 100 000 and 1 : 10 000 in the adult population [7]. Most CVID patients receive immunoglobulin (Ig)G substitution, which has a significant impact on health-related quality of life [8,9]. Previous studies have shown that there are subgroups of patients with CVID with respect to their genotype, B cell or T cell profiles and clinical phenotypes [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%